IMPLEMENTASI PENGABDIAN KEPADA MASYARAKAT MAHASISWA UNWIDHA MELALUI KEGIATAN KKN DI DESA MALANGJIWAN - Putri Zudhah Ferryka; Salma Nanda Ardelia; Gloria Yulianti; Annisa Nur Shafa; Devina Putri Ashani; Icha Putri Salsabila; Perwita Sari; Aulia Fiitri Ananda; Alice Stefandrea Dhyani Pratista; Anisa Martha Kustanti; Tyara Rahmyanesti; Monicha Anggrahini Wahyuningtias; Teghar Dian Antono; Muhammad Noval Romadhon; Muhammad Khamal Arifin; Dwi Yoga Raditya Dharma Putra (LPPM Universitas Widya Dharma Klaten, 2026)
The 2025 Widya Dharma University Klaten Community Service Program (KKN) will be held from August 1, 2025, to August 31, 2025. Group 17 will be located in Malangjiwan Village, Kebonarum District, Klaten Regency, Central Java Province. The goal of this KKN program is to increase students' social awareness of community issues and empower them through programs based on local potential and needs. The KKN program for group 17 at Widya Dharma University Klaten includes: first, digital promotion through TikTok about water therapy at Umbul Brintik; second, realizing food security through hydroponics; third, digitalization of MSMEs through the Capcut application; fourth, earthquake disaster response with the Klaten Regional Disaster Management Agency (BPBD); and many more.